1997
DOI: 10.3171/jns.1997.86.5.0845
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea for treatment of unresectable and recurrent meningiomas. I. Inhibition of primary human meningioma cells in culture and in meningioma transplants by induction of the apoptotic pathway

Abstract: Meningiomas, which invade intracranial bone structures and the adjacent connective tissue, are frequently unresectable because of their aggressive and recalcitrant growth behavior. They have a high recurrence rate, and in approximately 10% of these tumors there is an increased risk of malignancy. Significant morbidity and mortality rates associated with recurrent meningiomas demand nonsurgical approaches. To date, adjuvant hormonal treatment has not proven beneficial. The anticancer drug hydroxyurea was theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 52 publications
0
47
0
1
Order By: Relevance
“…Recently, hydroxyurea, a ribonucleotide reductase inhibitor, was used in adjuvant chemotherapy for patients with recurrent or unresectable meningioma, and was effective in halting the growth of enlarging benign meningiomas but not malignant meningiomas. 21,28,31) Hydroxyurea may inhibit the growth of meningioma cell lines through an apoptotic mechanism. 30) Interestingly, in vitro exposure of renal cancer cells to low-dose hydroxyurea causes loss of chromosomal aberration, decrease in the number of MDR-1 gene copies, and increased sensitivity to vinblastine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hydroxyurea, a ribonucleotide reductase inhibitor, was used in adjuvant chemotherapy for patients with recurrent or unresectable meningioma, and was effective in halting the growth of enlarging benign meningiomas but not malignant meningiomas. 21,28,31) Hydroxyurea may inhibit the growth of meningioma cell lines through an apoptotic mechanism. 30) Interestingly, in vitro exposure of renal cancer cells to low-dose hydroxyurea causes loss of chromosomal aberration, decrease in the number of MDR-1 gene copies, and increased sensitivity to vinblastine.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The decision to introduce hydroxyurea in the treatment of unresectable and recurrent meningiomas was ultimately based on our experimental findings in cell cultures and in tumor cell transplants in nude mice, which demonstrated that hydroxyurea stopped cell growth by triggering the apoptotic cascade. [31,32] Hydroxyurea has never been used in the treatment of meningiomas and response rates of up to 70% within 1 year of initiation of oral administration reflect extraordinary success in the treatment of this solid tumor. By analogy with our experimental data, [31,32] we suggest that induction of apoptosis is also the cause of tumor regression in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Hydroxyurea has never been used in the treatment of meningiomas and response rates of up to 70% within 1 year of initiation of oral administration reflect extraordinary success in the treatment of this solid tumor. By analogy with our experimental data, [31,32] we suggest that induction of apoptosis is also the cause of tumor regression in our patients. The activation of this mechanism gives hope that long-term treatment with hydroxyurea can lead to a true remission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se analizaron fármacos correspondientes a familias distintas de quimioterápicos, algunos de uso habitual en determinados tumores, donde ya han mostrado su eficacia 4,17,18 , todos ellos con un margen de concentración de 10-2 hasta 10-12 M.…”
Section: Fármacos a Analizarunclassified